Review of Eotrogaspidia Lelej (Hymenoptera: Mutillidae: Trogaspidiini) - Okayasu, Juriya; Lelej, Arkady S.; Williams, Kevin A. (Zootaxa, 2021)
Ten species of Eotrogaspidia Lelej, 1996, two related species of Trogaspidia Ashmead, 1899 and one related species of Vanhartenidia Lelej in Lelej & van Harten, 2006 are revised. Before this study, Eotrogaspidia included the following four species: E. amans (André, 1909) (♂♀), E. auroguttata (Smith, 1855) (♂♀), E. ekka (Nurse, 1902) (♀) and E. oryzae (Pagden, 1934) (♂♀). In the present paper, four new species are described: E. adhabar sp. nov. (♂) (India, Nepal), E. buddha sp. nov. (♂♀) (India, Nepal, Pakistan, Sri Lanka), E. hauseri sp. nov. (♂) (India, Nepal) and E. melanopleura sp. nov. (♀) (China). Three species are transferred to Eotrogaspidia from Trogaspidia: E. lena (Cameron, 1899), comb. nov. (♂), E. rubripes (André, 1901), comb. nov. (♀) and E. saussurei (Lelej, 2005), comb. nov. (♂♀). Mutilla ekka Nurse, 1902 from India is transferred from Eotrogaspidia to Vanhartenidia ekka, comb. nov. The male of E. saussurei is described. New synonymies are proposed for E. auroguttata (= T. vallicola Tsuneki, 1993, syn. nov.) and Trogaspidia mackieae (Cockerell, 1928) (= T. pacifica Tsuneki, 1972, syn. nov.). Eight new country records are presented: one from China, two from Laos, one from Vietnam, two from India, one from Iran, and one from Afghanistan. Female specimens of E. buddha sp. nov. were formerly misidentified as T. acidalia (Cameron, 1897), stat. resurr. by the late B. Petersen. The lectotype of T. acidalia is designated and illustrated to clarify its identity. Diagnoses and illustrations for reviewed species and a key to all known Eotrogaspidia species and related genera are provided for males and females.